Promoting Learners` Autonomy Through Individualized Learning - Endang Fauziati (Bina Nusantara University, 2007)
Article basically tries to explore the concept of individualized learning applicable in teaching learning process which can enhance learners’ autonomy and provides a brief practical guidance on how to put this concept into classroom practices. There are at least five underlying assumptions of learning based on this concept, namely: different learning styles, a variety of sources, teacher as facilitator, integrated learning tasks, and different learning goals. It can be concluded that classroom practices designed based on these concepts can improve learners’ autonomy, such as grouping, projects or tasks, and discussion.